Inhaled hydrogen sulfide prevents neuropathic pain after peripheral nerve injury in mice - Kida, Kotaro (Nitric Oxide, 2014)
Increasing evidence suggests that the pathogenesis of neuropathic pain is mediated through activation of microglia in the spinal cord. Hydrogen sulfide attenuates microglial activation and central nervous system inflammation; however, the role of hydrogen sulfide in neuropathic pain is unclear. In this study, we examined the effects of hydrogen sulfide breathing on neuropathic pain in mice. C57BL/6J mice were subjected to chronic constriction injury (CCI) of the sciatic nerve. After CCI, mice breathed air alone or air mixed with hydrogen sulfide at 40 ppm for 8 h on 7 consecutive days. The expression levels of inflammatory cytokines including interleukin 6 (IL-6) were measured in the spinal cord. Effects of hydrogen sulfide on IL-6-induced activation of microglia were examined in primary rat microglia. Mice that breathed air alone exhibited the neuropathic pain behavior including mechanical allodynia and thermal hyperalgesia and increased mRNA levels of IL-6 and chemokine CC motif ligand 2 (CCL2) after CCI. Inhaled hydrogen sulfide prevented the neuropathic pain behavior and attenuated the upregulation of inflammatory cytokines. Sodium sulfide inhibited IL-6-induced activation of primary microglia. These results suggest that inhaled hydrogen sulfide prevents the development of neuropathic pain in mice possibly via inhibition of the activation of microglia in the spinal cord.